VALUE ADDED TAX AND GROSS FIXED CAPITAL FORMATION IN NIGERIA (Journal of Global Accounting, 2026)
This study assessed the effect of value added tax on gross fixed capital formation in Nigeria for a period of twenty years spanning from 2006 to 2025. Ex-Post facto research design was adopted. The time series data were obtained from Federal Inland Revenue Services, Central Bank of Nigeria, National Bureau of Statistics and the World Bank Publications. As a preliminary step in testing, the study employed the Augmented Dickey-Fuller (ADF) Unit root test to confirm the order of integration of the time series variables. The study employed Ordinary Least Square (OLS) regression analysis. In conclusion, the study found that value added tax has a significant and positive effect on gross fixed capital formation in Nigeria at 5% level of significance. It was recommended that the Federal Government should see that the application of value added tax ensures that international trade takes place on a transparent basis and avoids distortions like tax cascading associated with alternative commodity taxes devise means of curbing corruption and leakages in the petroleum profit tax administration.
Keywords: Gross Fixed Capital Formation; Tax Reform; Value Added Tax